Characteristics of a Constructivist Classroom in the Context of Science Education - Prabha, Shashi (JOURNAL OF INDIAN EDUCATION, 2010)
A constructivist classroom of science exhibits some marked features that are different from a traditional classroom. National Curriculum Framework-2005 emphasises on an environment in the science classroom which is conducive for constructivist learning. The classroom environment is maintained in such a way that students actively participate in learning which involves inventing and constructing knowledge and new ideas. Teacher applies various approaches to teaching learning process in order to make her students inquisitive thinkers, who question, reason, reflect, make association with prior learning, imagine and think. In the present paper some characteristics of a constructivist classroom in the context of science education are discussed.